Anxiety and Depression in Patients With Pulmonary Arterial Hypertension in Northwest China: A Cross-Sectional Study - Zhang, Juxia; Yin, Yuhuan; Wen, Yujie; Shi, Fugui; Wang, Jiancheng (Frontiers in Psychiatry, 2022)
Objective Pulmonary arterial hypertension (PAH) is a rare life-threatening and incurable disease. Although symptoms of depression and anxiety have been widely reported, these traits and associated factors have not been systematically assessed in Northwest China. Methods A cross-sectional study was conducted between March 2020 and February 2021. 106 PAH patients in Northwest China were evaluated by Self-rating Anxiety Scale (SAS) and the Self Rating Depression Scale (SDS) questionnaire. Results Overall, the included patients had particularly high depressive symptoms (70.09%), while anxiety among them was 17.55%. Multivariate linear regression revealed that patients with lower age (p = 0.04), female (p< 0.01), smoking (p< 0.01), WHO functional class III/IV (p< 0.01), higher mean pulmonary hypertension (p< 0.01), lower left ventricular ejection fraction (p< 0.01), and lower 6-min walking distance (p< 0.01) had higher anxiety scores. Patients who lived in rural areas (p = 0.01), smoking (p< 0.01), WHO functional class III/IV (p< 0.01), higher mean pulmonary hypertension (p = 0.04), lower 6-min walking distance (p< 0.01), and college degree or above had higher depression scores (p = 0.02). Conclusions Mental health problems such as depression are common among patients with PAH in Northwest China. Patients' characteristics such as smoking status, WHO functional class, and 6-min walking distance were related to anxiety and depression scores. Thus, early detection of mental health problems such as depression and anxiety should be detected in PAH patients. Meanwhile, interventions against these problems should be used to improve such patients' mental status.